Well-being and Pregnancy - Pallavi Talukdar; Arunjyoti Baruah (Indian Journal of Psychiatric Nursing)
Well-being is a complex construct on the optimal functioning in one's life. Well-being is basically having two perspectives: hedonic approach (i.e., pain avoidance and pleasure attainment) and eudaimonic approach (i.e., living up to one's fullest potential). Over the years, researchers have explored various stages of one's life based on these approaches. Pregnancy is an important milestone of women's life. Pregnancy is a period of hope and growth. This concept paper has been drafted with the aim of having an understanding regarding well-being and its short-term as well as long-term impact on pregnant women and their unborn children. The objectives of the study were to get an overview on well-being and to understand its effect on pregnant women as well as their fetuses. The electronic literature search engines used were Google Scholar and PubMed for selecting papers related to the theme well-being and pregnancy. Again, these selected articles were further screened for more relevant literature. For the present paper, a total of 35 articles were reviewed which were published online. Assessment of well-being during pregnancy helps in the assurance of better future for both the mother and the child. In this paper, the researcher has looked into a comprehensive view of well-being, and this has an influence on the pregnant women. This understanding will help in the promotion of well-being and maternal health, which in turn will have a positive effect on the baby.